Neonatal Escherichia coli infection in twins: clinical spectrum and management dilemma. Issue 1 (27th January 2021) - Ehman, Dylan; Mugarab Samedi, Veronica; Kalaniti, Kaarthigeyan; Daspal, Sibasis
Abstract : The clinical manifestation of Escherichia coli could vary from asymptomatic bacteraemia to systemic bloodstream infection and meningitis. We describe an unusual course of E. coli infection in twins, emphasising commencement of appropriate antimicrobial therapy. A set of male dichorionic diamniotic twins were delivered at 34 weeks of gestation by caesarian section. Pregnancy was complicated by diabetes, pre-eclampsia and cholestasis. Antenatal ultrasounds noted a congenital pulmonary airway malformation in twin A. Following delivery, twin A developed respiratory distress, but twin B was asymptomatic. Partial septic work-up at admission in the neonatal intensve care unit was done. Twin A's blood culture grew E. coli, while twin B's blood culture was negative. Twin A was treated with 7 days of intravenous antibiotics. At 11 days of age, twin B acutely developed a scrotal swelling. On suspicion of testicular torsion, he was taken for urgent surgery, which revealed a scrotal abscess positive for E. coli . The scrotum was irrigated and successfully treated with 4 weeks of antibiotics. Both twins were doing well at 3 months of follow-up.